A kind of ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire and preparation method thereof

By adding specific microalloyed elements and slow diffusion elements to Cu-Ni-Sn alloys, and using vacuum continuous casting and multi-stage deformation heat treatment processes, ultra-high strength resistance with high strength, conductivity and high temperature resistance are prepared by using the following processes. High-temperature Cu-Ni-Sn alloy wire solves the problems of poor composition segregation and high-temperature conductivity stability in the preparation process of existing alloy materials, achieving significant improvement in performance and wide application potential.

CN118006965BActive Publication Date: 2025-02-18GRIMAT ENG INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410145090.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-01
Publication Date
2025-02-18
Estimated Expiration
2044-02-01

AI Technical Summary

Technical Problem

During the preparation process, existing Cu-Ni-Sn alloy materials are prone to component segregation, discontinuous precipitation and cracking, resulting in uneven performance and poor high-temperature conductivity stability, which limits its wide application.

Method used

By adding Si, Ti, V, Co microalloying elements to Cu-Ni-Sn alloy, and adding slow diffusion elements Nb and/or Ta and trace amounts of rare earth elements, vacuum continuous casting and multi-stage deformation heat treatment technology are used. , ultra-high strength high temperature resistance Cu-Ni-Sn alloy wire with uniform composition, strong (111) silk texture and high special grain boundary number were prepared.

Benefits of technology

The high strength, conductivity and high temperature resistance of Cu-Ni-Sn alloy wire has been achieved, the tensile strength reaches more than 1400MPa, the oxidation weight gain of 850℃/1h is ≤0.1mg/cm2, and the conductivity is above 10% IACS, which is suitable for 5G communication, aerospace, new energy vehicles and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118006965B_ABST
    Figure CN118006965B_ABST
Patent Text Reader

Abstract

The present invention provides an ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire and a preparation method thereof, and relates to the technical field of copper alloys. The Cu-Ni-Sn alloy wire prepared by the present invention has a small and uniform grain size, an average grain size between 2 and 5 μm, a tensile strength of more than 1400 MPa, a number of special grain boundaries (low ΣCSL) of more than 40%, good high temperature oxidation resistance, and an oxidation weight gain of ≤0.1 mg / cm at 850°C / 1h. 2 By controlling the continuous casting and drawing annealing process, the obtained organization has a strong (111) silk texture, and the conductivity can reach 10% IACS, which can be used in electrical connectors in 5G communications, aerospace or smart terminals. The results of the examples show that the preparation method provided by the present invention has the characteristics of high batch stability, uniform performance, low energy consumption, high yield rate, low cost, and short processing flow, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copper alloys, and in particular to an ultra-high-strength and high-temperature-resistant Cu-Ni-Sn alloy wire and a preparation method thereof. Background Art

[0002] Ultra-high-strength conductive elastic copper alloy is widely used in the production of conductive elastic components such as pins, switches, contact springs, and terminals due to its good electrical conductivity, thermal conductivity, high strength, and high temperature resistance. Beryllium copper is known as the "king of non-ferrous elastic materials" and is the main material for high-performance elastic components of high-end electrical connectors at this stage. However, its preparation process is prone to produce toxic dust, and its stress relaxation resistance is poor at high temperatures, and its high-temperature electrical conductivity stability is low. In addition, the deformation of the components after aging is large, resulting in a complex production process and high production costs, which limits its further expansion of applications.

[0003] Cu-Ni-Sn alloy is a copper alloy material with high strength, high elasticity, high temperature resistance, stress relaxation resistance, wear resistance and corrosion resistance. Its high temperature stress relaxation rate is much lower than that of beryllium copper, and it is the most potential material to replace beryllium copper. However, this material has high strength and poor plasticity, is easy to break during wire drawing, and is difficult to prepare and process. In addition, due to the high content of alloy element Sn and limited solid solubility in copper, when Cu-Ni-Sn alloy is prepared by melt casting method, serious Sn segregation is easy to occur, which cannot be eliminated by subsequent solid solution treatment, which will seriously affect the comprehensive performance of the material. Secondly, Cu-Ni-Sn alloy is prone to discontinuous precipitation in the later stage of aging. In addition, due to the inhomogeneity of composition and organization and the large intrinsic internal stress of the alloy, the alloy cracks during the deformation heat treatment process, which seriously affects the quality and yield of the product. Summary of the invention

[0004] The object of the present invention is to provide an ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire and a preparation method thereof. The Cu-Ni-Sn alloy wire prepared by the present invention has uniform tissue composition, high strength, electrical conductivity and high temperature resistance.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides an ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire, which comprises, by mass percentage, 14-16% Ni, 6-8% Sn, 0.2-0.5% microalloying elements, 0.01-0.1% rare earth elements, 0.05-0.2% Ta and / or Nb, and the balance Cu;

[0007] The microalloying elements include one or two of Co, Si, Ti and V;

[0008] The ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire has an average grain size of 2 to 5 μm, a number of special grain boundaries of more than 40%, and a (111) wire texture.

[0009] Preferably, the rare earth element includes La, Ce, Sc or Gd.

[0010] Preferably, the tensile strength of the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire is above 1400 MPa, and the oxidation weight gain at 850°C / 1h is ≤0.1 mg / cm 2 , conductivity is above 10% IACS.

[0011] The present invention provides a method for preparing the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire described in the above scheme, comprising the following steps:

[0012] Corresponding to the composition of the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire, each prepared raw material is subjected to vacuum downward continuous casting to obtain a rod blank; the vacuum downward continuous casting conditions include: a casting temperature of 1150-1250° C., a pull-stop time ratio of 1:3-1:6, a downward speed of 0.2-1 mm / s, a cooling water inlet temperature of 15-20° C., and a water outlet temperature of 25-30° C.;

[0013] The rod blank is subjected to a homogenization treatment to obtain a homogenized rod blank; the homogenization treatment temperature is 800-900° C., and the heat preservation time is 4-6 hours;

[0014] The homogenized rod blank is subjected to a first cold drawing to obtain a first drawn wire; the first cold drawing is a multi-pass cold drawing, and the total processing rate of the first cold drawing is 80-90%;

[0015] The first drawn wire is subjected to a solution treatment to obtain a solution wire; the solution treatment temperature is 850 to 950° C., and the holding time is 5 to 10 minutes;

[0016] The solid solution wire is subjected to a second cold drawing to obtain a second drawn wire; the second cold drawing is a multi-pass cold drawing, and the total processing rate of the second cold drawing is 90 to 99.9%;

[0017] The second drawn wire is subjected to aging treatment to obtain the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire; the aging treatment temperature is 400-500° C., and the insulation time is 5-10 minutes.

[0018] Preferably, after obtaining the second drawn wire, the method further includes winding the second drawn wire on a copper wire spool and performing an aging treatment in a manner of winding the second drawn wire on the spool.

[0019] Preferably, a groove is formed on the copper wire shaft along the axial direction.

[0020] Preferably, the crucible and crystallizer used in the vacuum continuous casting are made of boron nitride.

[0021] Preferably, the cooling method of the homogenization treatment is water cooling.

[0022] Preferably, the cooling method of the solution treatment is water cooling.

[0023] Preferably, the cooling method of the aging treatment is air cooling.

[0024] The invention provides an ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire, which comprises, by mass percentage, 14-16% Ni, 6-8% Sn, 0.2-0.5% microalloying elements, 0.01-0.1% rare earth elements, 0.05-0.2% Ta and / or Nb, and the balance Cu; the microalloying elements comprise one or two of Co, Si, Ti and V; the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire has an average grain size of 2-5 μm, a number of special grain boundaries of more than 40%, and has a (111) wire texture.

[0025] Compared with the existing common Cu-Ni-Sn alloy, the present invention can effectively improve the segregation of Cu-Ni-Sn alloy components and curb discontinuous precipitation by adding and reasonably adjusting Si, Ti, V, and Co microalloying elements; at the same time, slow diffusion elements Nb and / or Ta and trace amounts of rare earth elements are added to improve the high temperature resistance of the material, making the Cu-Ni-Sn alloy less prone to oxidation during high temperature applications. The Cu-Ni-Sn alloy prepared by the present invention has a small grain size and good uniformity, an average grain size of 2 to 5 μm, and a number of special grain boundaries (low ΣCSL) of more than 40% (such as Figure 1 As shown in Figure 2, compared with random grain boundaries, low ΣCSL grain boundaries have lower free volume energy and stronger resistance to high temperature intergranular oxidation, which can improve the high temperature oxidation resistance of the alloy. The results of the embodiment show that the tensile strength of the Cu-Ni-Sn alloy wire provided by the present invention can reach more than 1400MPa, and it has good resistance to high temperature oxidation, and the oxidation weight gain at 850℃ / 1h is ≤0.1mg / cm 2 The conductivity can reach more than 10% IACS, and it can be used in 5G communications, aerospace, new energy vehicles, rail transit or smart terminals.

[0026] The present invention provides a method for preparing the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire described in the above scheme, which sequentially adopts vacuum down-drawing continuous casting → homogenization → first cold drawing → solution treatment → second cold drawing → aging treatment to obtain the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire.

[0027] The present invention avoids the problems of poor product batch stability, poor performance uniformity, high energy consumption, long processing flow, etc. caused by the slight difference in chemical composition between ingots produced by the traditional vacuum metallurgical method, which is to prepare copper-nickel-tin ingots and then prepare alloy billets (rods, wires, plates, strips) through pressure processing such as extrusion or hot rolling. The present invention is based on vacuum downcasting technology, and by adjusting the core process parameters, the melt cooling intensity is increased, so that the alloy obtains supersaturation in the downcasting process, and the segregation of Sn elements is prevented; at the same time, by controlling the downcasting process parameters, regulating the grain orientation, and combining the later large deformation amount of cold deformation and short-time high-temperature heat treatment, a structure with a strong (111) wire texture is obtained, and the number of special grain boundaries (low ΣCSL) is more than 40%, so as to achieve the purpose of synergistically improving the strength, conductivity and high-temperature performance of the wire.

[0028] The present invention adopts appropriate homogenization and solution treatment processes, supplemented by a multi-stage deformation heat treatment method, to inhibit dendrite segregation and spindle structure coarsening, control the precipitation behavior of the solution phase and the discontinuous solution phase, and adjust the grain size and grain orientation, so as to achieve the purpose of optimizing the alloy structure and ensure the matching of its formability, mechanical and electrical properties.

[0029] The present invention adopts a technology combining multi-pass large deformation cold deformation with short-time annealing treatment to optimize the grain boundary characteristic distribution of the alloy. The copper-nickel-tin alloy prepared by the present invention has a small grain size and good uniformity, an average grain size between 2 and 5 μm, and the number of special grain boundaries (low ΣCSL) is more than 40%.

[0030] Furthermore, the present invention designs a bobbin for wire aging treatment, using pure copper as the raw material of the bobbin, which has a thermal expansion coefficient similar to that of the copper-nickel-tin alloy. When the copper-nickel-tin wire is wound on the bobbin for aging treatment, the copper-nickel-tin wire will not be deformed or broken due to the different thermal expansion coefficients of the two. Secondly, slots are cut on the bobbin, such as Figure 2 As shown, it is ensured that it and the copper-nickel-tin wire expand and contract together during the aging process, further avoiding the wire breakage due to thermal expansion and contraction during the annealing process. In addition, the wire is usually annealed online. Due to the long length of the wire, the aging time during the online aging process is long, and the use of online annealing is not conducive to industrial production. Therefore, the synchronous annealing treatment of the wire spool designed by the present invention shortens the aging time and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 EBSD results of Example 1, including (a) microstructure, (b) grain size distribution histogram, (c) (d) grain orientation diagram;

[0032] Figure 2 It is a schematic structural diagram of the copper wire spool used in the present invention. DETAILED DESCRIPTION

[0033] The present invention provides an ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire, which comprises, by mass percentage, 14-16% Ni, 6-8% Sn, 0.2-0.5% microalloying elements, 0.01-0.1% rare earth elements, 0.05-0.2% Ta and / or Nb, and the balance Cu;

[0034] The microalloying elements include one or two of Co, Si, Ti and V;

[0035] The ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire has an average grain size of 2 to 5 μm, a number of special grain boundaries of more than 40%, and a (111) wire texture.

[0036] Calculated by mass percentage, the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire provided by the present invention comprises Ni 14-16%, preferably 14.5-15.5%, and more preferably 14.8-15.2%.

[0037] Calculated by mass percentage, the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire provided by the present invention comprises Sn 6-8%, preferably 6.5-7.5%, and more preferably 6.8-7.2%.

[0038] In terms of mass percentage, the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire provided by the present invention includes 0.2-0.5% of microalloying elements, preferably 0.25-0.45%, and more preferably 0.3-0.4%. In the present invention, the microalloying elements include one or two of Co, Si, Ti and V; when the microalloying elements include two of the above elements, the present invention has no special requirements for the ratio of each element, and any ratio is acceptable. The present invention can effectively improve the segregation of Cu-Ni-Sn alloy components and curb discontinuous precipitation by adding and reasonably adjusting Si, Ti, V, and Co microalloying elements.

[0039] The ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire provided by the present invention comprises 0.01-0.1% rare earth elements, preferably 0.02-0.09%, and more preferably 0.04-0.07%, by mass percentage. In the present invention, the rare earth elements preferably include La, Ce, Sc or Gd.

[0040] In terms of mass percentage, the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire provided by the present invention includes Ta and / or Nb 0.05-0.2%, preferably 0.08-0.16%, and more preferably 0.1-0.14%. When the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire includes Ta and Nb at the same time, the present invention has no special requirements for the ratio of the two, and any ratio is acceptable. The present invention adds the slow diffusion element Nb and / or Ta and a trace amount of rare earth elements to improve the high temperature resistance of the material, so that the Cu-Ni-Sn alloy is not easily oxidized when used at high temperatures.

[0041] Measured by mass percentage, the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire provided by the present invention also includes a surplus of Cu and unavoidable impurities.

[0042] In the present invention, the average grain size of the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire is preferably 2-5 μm; the number of special grain boundaries is preferably above 40%, more preferably 40-65%; it has a strong (111) wire texture, and the proportion of the (111) wire texture is preferably above 45%, more preferably 45-65%. The small and uniform grain size is conducive to improving the tensile strength of the Cu-Ni-Sn alloy wire; compared with random grain boundaries, the free volume energy of low ΣCSL grain boundaries is lower, and it has stronger resistance to high temperature intergranular oxidation, which can improve the high temperature oxidation resistance of the alloy; the strong (111) wire texture is conducive to improving the electrical conductivity of the Cu-Ni-Sn alloy wire.

[0043] In the present invention, the tensile strength of the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire is above 1400MPa, and the oxidation weight gain at 850℃ / 1h is ≤0.1mg / cm 2 , the conductivity is above 10% IACS, and it can be applied in 5G communications, aerospace, new energy vehicles, rail transit or smart terminals. The conductivity can reach more than 10% IACS.

[0044] The present invention provides a method for preparing the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire described in the above scheme, comprising the following steps:

[0045] Corresponding to the composition of the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire, each prepared raw material is subjected to vacuum downward continuous casting to obtain a rod blank; the vacuum downward continuous casting conditions include: a casting temperature of 1150-1250° C., a pull-stop time ratio of 1:3-1:6, a downward speed of 0.2-1 mm / s, a cooling water inlet temperature of 15-20° C., and a water outlet temperature of 25-30° C.;

[0046] The rod blank is subjected to a homogenization treatment to obtain a homogenized rod blank; the homogenization treatment temperature is 800-900° C., and the heat preservation time is 4-6 hours;

[0047] The homogenized rod blank is subjected to a first cold drawing to obtain a first drawn wire; the first cold drawing is a multi-pass cold drawing, and the total processing rate of the first cold drawing is 80-90%;

[0048] The first drawn wire is subjected to a solution treatment to obtain a solution wire; the solution treatment temperature is 850 to 950° C., and the holding time is 5 to 10 minutes;

[0049] The solid solution wire is subjected to a second cold drawing to obtain a second drawn wire; the second cold drawing is a multi-pass cold drawing, and the total processing rate of the second cold drawing is 90 to 99.9%;

[0050] The second drawn wire is subjected to aging treatment to obtain the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire; the aging treatment temperature is 400-500° C., and the insulation time is 5-10 minutes.

[0051] The invention corresponds to the composition of the ultra-high-strength and high-temperature-resistant Cu-Ni-Sn alloy wire material, and performs vacuum downward continuous casting on each prepared raw material to obtain a rod blank.

[0052] In the present invention, the preparation raw materials preferably include one or two of pure cobalt, pure silicon, sponge titanium and pure vanadium, electrolytic copper, electrolytic nickel, pure tin, copper rare earth element master alloy, copper tantalum and / or copper niobium master alloy; the copper rare earth element master alloy is specifically one of copper lanthanum, copper cerium, copper gadolinium and copper scandium master alloy.

[0053] In the present invention, the vacuum down-casting preferably includes: placing the prepared raw materials in a crucible, placing the crucible containing the prepared raw materials in a vacuum down-casting furnace, passing high-purity argon gas in the furnace for protection, raising the temperature to 1200-1350°C, and after the prepared raw materials are completely melted, keeping the temperature for 0.5-1h, turning on the lead rod mode, and the resulting melt will enter the crystallizer for solidification. In the present invention, the material of the crucible and the crystallizer is preferably boron nitride. The present invention uses a boron nitride crucible and a crystallizer, which can effectively control the content of impurity elements and prevent the raw materials from reacting with the crucible and the crystallizer.

[0054] In the present invention, the casting temperature of the vacuum downward continuous casting is 1150-1250°C, preferably 1170-1230°C, and more preferably 1180-1210°C; the pull-stop time ratio is 1:3-1:6, and preferably 1:4-1:5; the downward speed is 0.2-1 mm / s, and preferably 0.4-0.8 mm / s, and more preferably 0.5-0.6 mm / s; the cooling water inlet temperature is 15-20°C, and preferably 16-19°C; the outlet temperature is 25-30°C, and preferably 26-28°C.

[0055] The present invention is based on vacuum down-casting continuous casting technology. By adjusting core process parameters, the solution cooling intensity is increased, so that the alloy obtains supersaturation in the down-casting process and prevents the segregation of Sn elements. At the same time, by controlling the down-casting process parameters, the grain orientation is regulated, and combined with the later large deformation amount of cold deformation and short-time high-temperature heat treatment, a structure with a strong (111) wire texture is obtained, and the number of special grain boundaries (low ΣCSL) is more than 40%, so as to achieve the purpose of synergistically improving the strength, conductivity and high-temperature performance of the wire.

[0056] The present invention has no special requirements on the size of the rod blank, and any size known in the art can be used. In an embodiment of the present invention, the diameter of the rod blank is 8 mm, 10 mm or 12 mm.

[0057] After obtaining the rod blank, the present invention performs homogenization treatment on the rod blank to obtain a homogenized rod blank.

[0058] In the present invention, the temperature of the homogenization treatment is 800-900°C, preferably 820-880°C, more preferably 840-860°C; the insulation time is 4-6h, preferably 4.5-5.5h, more preferably 5h; and the cooling method is preferably water cooling.

[0059] After obtaining the homogenized rod blank, the present invention performs a first cold drawing on the homogenized rod blank to obtain a first drawn wire.

[0060] In the present invention, the first cold drawing is a multi-pass cold drawing, and the total processing rate of the first cold drawing is 80-90%, preferably 82-88%, and more preferably 84-86%.

[0061] After obtaining the first drawn wire, the present invention performs a solid solution treatment on the first drawn wire to obtain a solid solution wire.

[0062] In the present invention, the temperature of the solution treatment is 850-950°C, preferably 870-930°C, and more preferably 890-910°C; the holding time of the solution treatment is 5-10min, preferably 6-9min, and more preferably 7-8min; the cooling method of the solution treatment is preferably water cooling.

[0063] After obtaining the solid solution wire, the present invention performs a second cold drawing on the solid solution wire to obtain a second drawn wire.

[0064] In the present invention, the second cold drawing is a multi-pass cold drawing, and the total processing rate of the second cold drawing is 90-99.9%, preferably 91-98%, and more preferably 93-96%.

[0065] After obtaining the second cold-drawn wire, the present invention performs aging treatment on the second drawn wire to obtain the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire.

[0066] In the present invention, the temperature of the aging treatment is 400-500°C, preferably 420-480°C, and more preferably 440-460°C; the holding time of the aging treatment is 5-10 min, preferably 6-9 min, and more preferably 7-8 min; the cooling method of the aging treatment is preferably air cooling.

[0067] The present invention preferably winds the second drawn wire on a copper wire spool, and performs subsequent aging treatment in the manner of winding on the spool. In the present invention, the copper wire spool preferably has a groove (such as Figure 2 shown).

[0068] The present invention adopts pure copper as the raw material of the spool, which has a thermal expansion coefficient similar to that of the copper-nickel-tin alloy. When the copper-nickel-tin wire is wound on the spool for aging treatment, the copper-nickel-tin wire will not be deformed or broken due to the different thermal expansion coefficients of the two. Secondly, slots are cut on the spool, such as Figure 2 As shown, it is ensured that it and the copper-nickel-tin wire expand and contract together during the aging process, further avoiding the wire breakage due to thermal expansion and contraction during the annealing process. In addition, the wire is usually annealed online. Due to the long length of the wire, the aging time during the online aging process is long, and the use of online annealing is not conducive to industrial production. Therefore, the synchronous annealing treatment of the wire spool designed by the present invention shortens the aging time and improves production efficiency.

[0069] The present invention adopts appropriate homogenization and solution treatment processes, supplemented by a multi-stage deformation heat treatment method, to inhibit dendrite segregation and spindle structure coarsening, control the precipitation behavior of the solution phase and the discontinuous solution phase, and adjust the grain size and grain orientation, so as to achieve the purpose of optimizing the alloy structure and ensure the matching of its formability, mechanical and electrical properties.

[0070] The present invention adopts a technology combining multiple cold deformation with large deformation amount and short-time annealing treatment (i.e., aging treatment) to optimize the grain boundary characteristic distribution of the alloy. The copper-nickel-tin alloy prepared by the present invention has a small grain size and good uniformity, an average grain size between 2 and 5 μm, and the number of special grain boundaries (low ΣCSL) is more than 40%.

[0071] The invention controls the down-drawing continuous casting and drawing annealing processes to obtain a structure with a strong (111) wire texture.

[0072] The ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0073] Example 1

[0074] The composition of the alloy is shown in Example 1 in Table 1.

[0075] (1) Vacuum continuous casting: Add the prepared materials according to the proportion in the vacuum continuous casting furnace. In order to control the content of impurity elements and prevent the raw materials from reacting with the crucible, boron nitride crucible and crystallizer are selected. High-purity argon gas is passed through the furnace for protection. The temperature is raised to 1350°C. After the melt is completely melted, it is kept warm for 0.5h. The casting temperature is controlled at 1250°C, the pull-stop time ratio is 1:6, the pull-down speed is 0.2mm / s, the cooling water inlet temperature is 15°C, and the outlet temperature is 25°C. The rod blank with a diameter of 12mm is cast.

[0076] (2) Homogenization: The alloy rod billet is homogenized in a box-type resistance furnace at a homogenization temperature of 900°C for 4 hours and a cooling method of water cooling.

[0077] (3) First cold drawing: The homogenized rod blank is subjected to multiple cold drawing passes with a processing rate of 85%.

[0078] (4) Solution treatment: The copper wire after drawing is subjected to high temperature short-time solution treatment, the solution temperature is 950°C, the holding time is 5 minutes, and the cooling method is water cooling.

[0079] (5) Second cold drawing: The alloy wire after the solution treatment is subjected to multiple cold drawing passes with a processing rate of 99.9%, and the alloy wire is wound on a slotted copper wire reel.

[0080] (6) Aging: The alloy spool is placed in a vacuum annealing furnace for aging treatment at a temperature of 500° C. for 5 min and air cooling.

[0081] Example 2

[0082] The composition of the alloy is shown in Example 2 in Table 1.

[0083] (1) Vacuum continuous casting: Raw materials are added to the vacuum continuous casting furnace according to the ratio. In order to control the content of impurity elements and prevent the raw materials from reacting with the crucible, boron nitride crucibles and crystallizers are selected. High-purity argon gas is passed through the furnace for protection. The temperature is raised to 1200°C. After the melt is completely melted, it is kept warm for 1 hour. The casting temperature is controlled at 1150°C, the pull-stop time ratio is 1:3, the pull-down speed is 1 mm / s, the cooling water inlet temperature is 20°C, and the outlet temperature is 28°C. The rod blank with a diameter of 8 mm is cast.

[0084] (2) Homogenization: The alloy rod billet is homogenized in a box-type resistance furnace at a homogenization temperature of 800°C for 6 hours and a cooling method of water cooling.

[0085] (3) First cold drawing: The homogenized rod blank is subjected to multiple cold drawing passes, with a processing rate of 87%.

[0086] (4) Solution treatment: The copper wire after drawing is subjected to high temperature short-time solution treatment, the solution temperature is 850°C, the holding time is 10 minutes, and the cooling method is water cooling.

[0087] (5) Second cold drawing: The alloy wire after the solution treatment is subjected to multiple cold drawing passes with a processing rate of 98%, and the alloy wire is wound on a slotted copper wire reel.

[0088] (6) Aging: The alloy spool is placed in a vacuum annealing furnace for aging treatment at a temperature of 400°C for 10 min and air cooling.

[0089] Example 3

[0090] The composition of the alloy is shown in Example 3 in Table 1.

[0091] (1) Vacuum continuous casting: Raw materials are added to the vacuum continuous casting furnace according to the ratio. In order to control the content of impurity elements and prevent the raw materials from reacting with the crucible, boron nitride crucibles and crystallizers are selected. High-purity argon gas is passed through the furnace for protection. The temperature is raised to 1250°C. After the melt is completely melted, it is kept warm for 0.75h. The casting temperature is controlled at 1200°C, the pull-stop time ratio is 1:3, the pull-down speed is 0.8mm / s, the cooling water inlet temperature is 17°C, and the outlet temperature is 29°C. The rod blank with a diameter of 12mm is cast.

[0092] (2) Homogenization: The alloy rod billet is homogenized in a box-type resistance furnace at a homogenization temperature of 850°C for 5 h and a cooling method of water cooling.

[0093] (3) First cold drawing: The homogenized rod blank is subjected to multiple cold drawing passes with a processing rate of 90%.

[0094] (4) Solution treatment: The copper wire after drawing is subjected to high temperature short-time solution treatment, the solution temperature is 900°C, the holding time is 8 minutes, and the cooling method is water cooling.

[0095] (5) Second cold drawing: The alloy wire after the solution treatment is subjected to multiple cold drawing passes with a processing rate of 99%, and the alloy wire is wound on a slotted copper wire reel.

[0096] (6) Aging: The alloy spool is placed in a vacuum annealing furnace for aging treatment at a temperature of 475°C for 8 min and air cooling.

[0097] Example 4

[0098] The composition of the alloy is shown in Example 4 in Table 1.

[0099] (1) Vacuum continuous casting: Raw materials are added to the vacuum continuous casting furnace according to the ratio. In order to control the content of impurity elements and prevent the raw materials from reacting with the crucible, boron nitride crucibles and crystallizers are selected. High-purity argon gas is passed through the furnace for protection. The temperature is raised to 1275°C. After the melt is completely melted, it is kept warm for 0.5h. The casting temperature is controlled at 1200°C, the pull-stop time ratio is 1:6, the pull-down speed is 0.3mm / s, the cooling water inlet temperature is 15°C, and the outlet temperature is 26°C. The rod blank with a diameter of 10mm is cast.

[0100] (2) Homogenization: The alloy rod billet is homogenized in a box-type resistance furnace at a homogenization temperature of 850°C for 4 hours and a cooling method of water cooling.

[0101] (3) First cold drawing: The homogenized rod blank is subjected to multiple cold drawing passes with a processing rate of 90%.

[0102] (4) Solution treatment: The copper wire after drawing is subjected to high temperature short-time solution treatment, the solution temperature is 900°C, the holding time is 10 minutes, and the cooling method is water cooling.

[0103] (5) Second cold drawing: The alloy wire after the solution treatment is subjected to multiple cold drawing passes with a processing rate of 95%, and the alloy wire is wound on a slotted copper wire reel.

[0104] (6) Aging: The alloy spool is placed in a vacuum annealing furnace for aging treatment at a temperature of 450°C for 10 min and air cooling.

[0105] Example 5

[0106] The composition of the alloy is shown in Example 5 in Table 1.

[0107] (1) Vacuum continuous casting: Raw materials are added to the vacuum continuous casting furnace according to the ratio. In order to control the content of impurity elements and prevent the raw materials from reacting with the crucible, boron nitride crucibles and crystallizers are selected. High-purity argon gas is passed through the furnace for protection. The temperature is raised to 1225°C. After the melt is completely melted, it is kept warm for 1 hour. The casting temperature is controlled at 1200°C, the pull-stop time ratio is 1:4, the pull-down speed is 1 mm / s, the cooling water inlet temperature is 20°C, and the outlet temperature is 30°C. The rod blank with a diameter of 8 mm is cast.

[0108] (2) Homogenization: The alloy rod billet is homogenized in a box-type resistance furnace at a homogenization temperature of 800°C for 5 h and a cooling method of water cooling.

[0109] (3) First cold drawing: The homogenized rod blank is subjected to multiple cold drawing passes with a processing rate of 88%.

[0110] (4) Solution treatment: The copper wire after drawing is subjected to high temperature short-time solution treatment, the solution temperature is 900°C, the holding time is 8 minutes, and the cooling method is water cooling.

[0111] (5) Second cold drawing: The alloy wire after the solution treatment is subjected to multiple cold drawing passes with a processing rate of 99.5%, and the alloy wire is wound on a slotted copper wire reel.

[0112] (6) Aging: The alloy spool is placed in a vacuum annealing furnace for aging treatment at a temperature of 400°C for 10 min and air cooling.

[0113] Example 6

[0114] The composition of the alloy is shown in Example 6 in Table 1.

[0115] (1) Vacuum continuous casting: Raw materials are added to the vacuum continuous casting furnace according to the ratio. In order to control the content of impurity elements and prevent the raw materials from reacting with the crucible, boron nitride crucibles and crystallizers are selected. High-purity argon gas is passed through the furnace for protection. The temperature is raised to 1325°C. After the melt is completely melted, it is kept warm for 0.5h. The casting temperature is controlled at 1225°C, the pull-stop time ratio is 1:5, the pull-down speed is 0.5mm / s, the cooling water inlet temperature is 18°C, and the outlet temperature is 27°C. The rod blank with a diameter of 10mm is cast.

[0116] (2) Homogenization: The alloy rod billet is homogenized in a box-type resistance furnace at a homogenization temperature of 850°C for 6 hours and a cooling method of water cooling.

[0117] (3) First cold drawing: The homogenized rod blank is subjected to multiple cold drawing passes with a processing rate of 90%.

[0118] (4) Solution treatment: The copper wire after drawing is subjected to high temperature short-time solution treatment, the solution temperature is 950°C, the holding time is 5 minutes, and the cooling method is water cooling.

[0119] (5) Second cold drawing: The alloy wire after the solution treatment is subjected to multiple cold drawing passes with a processing rate of 98%, and the alloy wire is wound on a slotted copper wire reel.

[0120] (6) Aging: The alloy spool is placed in a vacuum annealing furnace for aging treatment at a temperature of 470° C. for 8 min and air cooling.

[0121] Example 7

[0122] The composition of the alloy is shown in Example 7 in Table 1.

[0123] (1) Vacuum continuous casting: Raw materials are added to the vacuum continuous casting furnace according to the ratio. In order to control the content of impurity elements and prevent the raw materials from reacting with the crucible, boron nitride crucibles and crystallizers are selected. High-purity argon gas is passed through the furnace for protection. The temperature is raised to 1250°C. After the melt is completely melted, it is kept warm for 0.5h. The casting temperature is controlled at 1150°C, the pull-stop time ratio is 1:3, the pull-down speed is 0.8mm / s, the cooling water inlet temperature is 19°C, and the outlet temperature is 30°C. The rod blank with a diameter of 8mm is cast.

[0124] (2) Homogenization: The alloy rod billet is homogenized in a box-type resistance furnace at a homogenization temperature of 800°C for 4 hours and a cooling method of water cooling.

[0125] (3) First cold drawing: The homogenized rod blank is subjected to multiple cold drawing passes with a processing rate of 85%.

[0126] (4) Solution treatment: The copper wire after drawing is subjected to high temperature short-time solution treatment, the solution temperature is 850°C, the holding time is 10 minutes, and the cooling method is water cooling.

[0127] (5) Second cold drawing: The alloy wire after the solution treatment is subjected to multiple cold drawing passes with a processing rate of 99.9%, and the alloy wire is wound on a slotted copper wire reel.

[0128] (6) Aging: The alloy spool is placed in a vacuum annealing furnace for aging treatment at a temperature of 400°C for 5 min and air cooling.

[0129] Table 1 Alloy composition formula of Examples 1 to 7 (wt%)

[0130]

[0131]

[0132] The Cu-Ni-Sn alloy wire of Example 1 was characterized by EBSD. Figure 1 , where (a) microstructure, (b) grain size distribution histogram, (c)(d) grain orientation diagram; Figure 1 It can be seen that the Cu-Ni-Sn alloy wire has fine grains and is evenly distributed, with an average grain size of 2.4 μm, a grain orientation of mainly (111), and a high proportion of special grain boundaries. The microstructure and properties of the Cu-Ni-Sn alloy wires prepared in Examples 1 to 7 are shown in Table 2.

[0133] Table 2 Microstructure and performance of Examples 1 to 7

[0134]

[0135] In Table 2, the test methods for various properties are as follows: the average grain size and (111) texture ratio are statistically characterized by EBSD; the tensile strength test method refers to GB / T 228.1-2010 "Metallic Materials Tensile Test Part 1: Room Temperature Test Method", the conductivity test method refers to GB / T 3048.4-2007 "Electrical Property Test Methods for Wires and Cables Part 4: Conductor DC Resistance Test", and the oxidation weight gain experiment refers to GB / T13303-1991 "Determination of Oxidation Resistance of Steel".

[0136] As can be seen from Table 2, the grain size of the Cu-Ni-Sn alloy wire prepared by the present invention is small and uniform, with an average grain size of 2 to 5 μm; the number of special grain boundaries is more than 40%, and it has a strong (111) wire texture. The small and uniform grain size is beneficial to improving the tensile strength of the Cu-Ni-Sn alloy wire; compared with random grain boundaries, the free volume energy of low ΣCSL grain boundaries is lower, and they have stronger resistance to high-temperature intergranular oxidation, which can improve the alloy's resistance to high-temperature oxidation; the strong (111) wire texture is beneficial to improving the electrical conductivity of the Cu-Ni-Sn alloy wire. Specifically, the tensile strength of the ultra-high-strength and high-temperature resistant Cu-Ni-Sn alloy wire is above 1400MPa, and the oxidation weight gain at 850℃ / 1h is ≤0.1mg / cm 2 , the conductivity is above 10% IACS, and it can be used in 5G communications, aerospace, new energy vehicles, rail transit or smart terminals.

[0137] The results of the examples show that the preparation method provided by the present invention has the characteristics of high batch stability, uniform performance, low energy consumption, high yield rate, low cost, and short processing flow, and has broad application prospects.

[0138] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire, characterized in that: Calculated by mass percentage, it includes Ni 14-16%, Sn 6-8%, microalloying elements 0.2-0.5%, rare earth elements 0.01-0.1%, Ta and / or Nb 0.05-0.2%, and the balance Cu; The microalloying elements include one or two of Co, Si, Ti and V; The ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire has an average grain size of 2-5 μm, a number of special grain boundaries of more than 40%, and a (111) wire texture; The method for preparing the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire comprises the following steps: Corresponding to the composition of the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire, each prepared raw material is subjected to vacuum downward continuous casting to obtain a rod blank; the vacuum downward continuous casting conditions include: a casting temperature of 1150-1250°C, a pull-stop time ratio of 1:3-1:6, a downward speed of 0.2-1 mm / s, a cooling water inlet temperature of 15-20°C, and a water outlet temperature of 25-30°C; The rod blank is subjected to a homogenization treatment to obtain a homogenized rod blank; the homogenization treatment temperature is 800-900° C., and the heat preservation time is 4-6 hours; The homogenized rod blank is subjected to a first cold drawing to obtain a first drawn wire; the first cold drawing is a multi-pass cold drawing, and the total processing rate of the first cold drawing is 80-90%; The first drawn wire is subjected to a solution treatment to obtain a solution wire; the solution treatment temperature is 850-950° C., and the holding time is 5-10 min; The solid solution wire is subjected to a second cold drawing to obtain a second drawn wire; the second cold drawing is a multi-pass cold drawing, and the total processing rate of the second cold drawing is 90-99.9%; The second drawn wire is subjected to aging treatment to obtain the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire; the aging treatment temperature is 400-500° C., and the insulation time is 5-10 minutes.

2. The ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire according to claim 1, characterized in that: The rare earth element includes La, Ce, Sc or Gd.

3. The ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire according to claim 1 or 2, characterized in that: The tensile strength of the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire is above 1400MPa, and the oxidation weight gain at 850℃ / 1h is ≤0.1mg / cm 2 , conductivity is above 10%IACS.

4. The method for preparing the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire according to any one of claims 1 to 3, comprising the following steps: Corresponding to the composition of the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire, each prepared raw material is subjected to vacuum bottom drawing continuous casting to obtain a rod blank; The conditions for the vacuum continuous casting include: a casting temperature of 1150-1250°C, a pull-stop time ratio of 1:3-1:6, a pull-down speed of 0.2-1 mm / s, a cooling water inlet temperature of 15-20°C, and a cooling water outlet temperature of 25-30°C; The rod blank is subjected to a homogenization treatment to obtain a homogenized rod blank; the homogenization treatment temperature is 800-900° C., and the heat preservation time is 4-6 hours; The homogenized rod blank is subjected to a first cold drawing to obtain a first drawn wire; the first cold drawing is a multi-pass cold drawing, and the total processing rate of the first cold drawing is 80-90%; The first drawn wire is subjected to a solution treatment to obtain a solution wire; the solution treatment temperature is 850-950° C., and the holding time is 5-10 min; The solid solution wire is subjected to a second cold drawing to obtain a second drawn wire; the second cold drawing is a multi-pass cold drawing, and the total processing rate of the second cold drawing is 90-99.9%; The second drawn wire is subjected to aging treatment to obtain the ultra-high strength and high temperature resistant Cu-Ni-Sn alloy wire; the aging treatment temperature is 400-500° C., and the insulation time is 5-10 minutes.

5. The preparation method according to claim 4, characterized in that: After obtaining the second drawn wire, the method further includes winding the second drawn wire on a copper wire spool and performing aging treatment in a manner of winding the second drawn wire on the spool.

6. The preparation method according to claim 5, characterized in that: The copper wire shaft is provided with a groove along the axial direction.

7. The preparation method according to claim 4, characterized in that: The crucible and the crystallizer used in the vacuum continuous casting are made of boron nitride.

8. The preparation method according to claim 4, characterized in that: The cooling method of the homogenization treatment is water cooling.

9. The preparation method according to claim 4, characterized in that: The cooling method of the solution treatment is water cooling.

10. The preparation method according to claim 4, characterized in that: The cooling method of the aging treatment is air cooling.

Citation Information

Patent Citations

  • High-temperature softening resistant Cu-Ni-Sn series high-strength and high-elasticity copper alloy and preparation method thereof

    CN114086027A

  • Preparation method and application of alloy wire

    CN115505765A